Cost of primary health care in the Republic of Serbia for the period 2006-2008 - Gajić-Stevanović Milena; Vukša Ana; Živković Slavoljub; Teodorović Nevenka (Serbian Medical Society - Dental Section, Belgrade, 2010)
Introduction. Primary health care in the Republic of Serbia is predominantly funded by the Republic Health Insurance Fund (RHIF). From the total income of health centers and institutes at the primary level, with no pharmacy and pharmacies (Kosovo excluded), 84% in 2008 was paid by RHIF. Frequency of participation ranged from 63-95% and it was stable in all observed years. The aim of this study was to determine the expenditures for primary health care for each insured person in statistically defined districts in the Republic of Serbia, with an emphasis on prevention participation. Material and Methods. Retrospective and comparative analysis of health statistics from the database of the Institute of Public Health of Serbia (IPHS) and financial data from the RHIF for the period 2006-2008 was done. Results. Observed by the districts in 2008, in Vojvodina, the lowest expenditure for primary health care had North Backa District (5,207 RSD) and greatest was in West Backa District (6,632 RSD) per capita. In the central Serbia territorial difference was much greater, ranging from 3,574 RSD in the District Morava to 6,701 RSD per capita in the District Toplica and Nisava. Expenditures for direct health care of RHIF per capita in the reporting period continuously have grown. Conclusion. The results showed that the largest cost for primary care for the insured person in the districts of Serbia was registered in the Nisava and Toplica (6,701 RSD) and lowest in the district of Morava (3,574 RSD) per capita.